About the Poetic Commentary "Nazmi Akaid" on the Works of Umar An-Nasafi "Akayd An-Nasafi" - Amonov Mukhtorjon Umarovich; Abdurahmon Latipov (Genius Publishing Group, 2022)
The article talks about "Nazmi Aqoid", a poetical commentary on Abu Hafs Umar anNasafi's work "Aqoid un-Nasafi". Among scholars, there are opinions that this work belongs to Alisher Navoi. But the poet did not give information about this work in the list of his works
Keywords: Aqoid science; Aqoid un-Nasafi; commentary on aqoid; Nazmi Aqoid